2014
DOI: 10.1155/2014/436482
|View full text |Cite
|
Sign up to set email alerts
|

Gyejigachulbu‐Tang Relieves Oxaliplatin‐Induced Neuropathic Cold and Mechanical Hypersensitivity in Rats via the Suppression of Spinal Glial Activation

Abstract: Activation of spinal glial cells plays a crucial role in the pathogenesis of neuropathic pain. An administration of oxaliplatin, an important anticancer drug, often induces acute neuropathic cold hypersensitivity and/or mechanical hypersensitivity in patients. Gyejigachulbu-tang (GBT), a herbal formula comprising Cinnamomi Cortex, Paeoniae Radix, Atractylodis Lanceae Rhizoma, Zizyphi Fructus, Glycyrrhizae Radix, Zingiberis Rhizoma, and Aconiti Tuber, has been used in East Asia to treat various pain symptoms, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…In our experiment, oral administration of Gyejigachulbu-Tang (200, 400, and 600 mg/kg for 5 days) markedly ameliorated mechanical-and cold-allodynia induced by oxaliplatin treatment. The formula possibly functions through the suppression of spinal glial activation [36]. We confirmed that the extract of Aconiti tuber could attenuate both cold and mechanical allodynia similar to Gyejigachulbu-Tang treatment.…”
Section: Gyejigachulbu-tang (Keishikajutsubuto In Japanese)supporting
confidence: 67%
See 1 more Smart Citation
“…In our experiment, oral administration of Gyejigachulbu-Tang (200, 400, and 600 mg/kg for 5 days) markedly ameliorated mechanical-and cold-allodynia induced by oxaliplatin treatment. The formula possibly functions through the suppression of spinal glial activation [36]. We confirmed that the extract of Aconiti tuber could attenuate both cold and mechanical allodynia similar to Gyejigachulbu-Tang treatment.…”
Section: Gyejigachulbu-tang (Keishikajutsubuto In Japanese)supporting
confidence: 67%
“…Oxaliplatin in rats Attenuates cold and mechanical allodynia Suppresses spinal glia activation [36] Gyeryongtongrac-Bang…”
Section: Gyejigachulbu-tangmentioning
confidence: 99%
“…This study prompts us to propose that, assuming that similar findings observed in this study occur in glial or glioma cells in vivo, any changes in the magnitude of functional [13,42]. Whether the activators of IK Ca channels or/and suppression of gap junction channels are effective at alleviating OXAL-induced neurotoxicity [23,34,41,43] necessitates further investigation.…”
Section: Discussionsupporting
confidence: 52%
“…OXALinduced inhibition of IK Ca -channel activity may be attributed to an interaction of the oxalate group embedded in this molecule with free Ca 2+ ions [42]. OXAL and its structurally related compounds would be intriguing pharmacological or toxicological tools used to characterize the IK Ca channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation